2021
DOI: 10.1007/s00103-021-03418-6
|View full text |Cite
|
Sign up to set email alerts
|

Bereitschaft zur COVID-19-Impfung unter Beschäftigten im Gesundheitswesen in Deutschland

Abstract: Zusammenfassung Hintergrund Die COVID-19-Pandemie stellt eine anhaltende Belastung für die Gesellschaft und das Gesundheitssystem dar. Die Bereitschaft des Gesundheitspersonals zur COVID-19-Impfung ist aufgrund seiner Schlüsselrolle in der Pandemiebewältigung besonders relevant. Ziel der Arbeit Die Studie untersuchte die Impfbereitschaft des Gesundheitspersonals in Deutschland in Abhängigkeit von soziodemografischen, berufsbezogenen und COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This high willingness of HW to be vaccinated has been confirmed in other studies [ 19 , 34 ]. However, an early survey started before the vaccines became available found that only 65% were inclined to be vaccinated [ 35 ]. Again, the SAH’s good communication strategy might have helped to create a positive attitude towards vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…This high willingness of HW to be vaccinated has been confirmed in other studies [ 19 , 34 ]. However, an early survey started before the vaccines became available found that only 65% were inclined to be vaccinated [ 35 ]. Again, the SAH’s good communication strategy might have helped to create a positive attitude towards vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Marciano et al (2022) reported that hope had a stronger and more consistent predictive power than did health, economic, security, and political threats on individuals' wellbeing, including depressive symptoms. Schug et al (2021) reported that social support and optimism had associations with low levels of depression and generalized anxiety. In addition, scholars found a negative association between trait optimism and depressive symptoms amid the pandemic.…”
Section: Positive Psychological Factors and Depressionmentioning
confidence: 99%
“…The German health care system was confronted with comparable circumstances at the beginning of the SARS-CoV‑2 pandemic in March 2020. Infection rates among health care workers were three times higher than the federal average [ 22 , 25 ]. The Robert Koch Institute informed weekly about the increasing number of SARS-CoV‑2 outbreaks in German hospitals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%